PERUBAHAN PENGGUNAAN LAHAN DI PROVINSI BALI - Abd. RAHMAN As-SYAKUR (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2011)
Research on land use change is very important to do in this time, because the land use change has an impacton physical and social environment. The purpose of this research is to determine the land use change in Baliprovince using satellite imagery data and GIS. Methods of this research are comparing the two data distribution ofland use in 2003 and 2008 obtained from interpretation of Landsat ETM+ (JICA, 2005) andALOS/ AVNIR-2.On-screen method is used to ALOS/ AVNIR-2 image data interpretation. Land use has changed between 2003and 2008. Settlements and irrigated ricefield is the most extensive land use changes, that are 2.553 ha and 2.553ha. W hereas the salting land use has not changed. Spatial representation shows in the south and central partof Bali Province is the region that have most experienced changes. Denpasar city and Badung Regency is twoadministrative regions which have most extensive experience in land use change.